A study of household stockholding change during 2008 financial crisis - Jin, Lulu (2013)
2008 financial crisis has negatively affected various economic compositions including stock market. Some research has been done to study households’ decisions on stock market during financial crisis by analyzing data from Panel Study of Income Dynamics(PSID). Using a different data set from Survey of Consumer Finances, this study is conducted to examine the significant characteristics that affect households’ decisions on stock market during the financial crisis and examine the consistency of significant factors obtained from PSID data. By investigating stock participation rate, persistency of stockholding status, and stock trading frequency respectively, we found that in general, wealthier households with well-educated risk-lover house heads, who belong to the majority race, tend to participate, stay in the stock market and trade more frequently during the crisis. Also households with different aged house heads, getting professional advice from financial planner, home ownership status and coverage of pension play important roles in households’ decisions in stock market. These significant characteristics of households are roughly the same with result obtained from PSID, which proves the consistency and importance of these factors in affecting households’ decisions of stock investment during the crisis.